Response of White Mice to Cells and Culture Constituents of Clostridium perfringens - Satterlee, L. D. (1969)
Broth cultures of Clostridium perfringens (ATCC 10543) were fractionated by ammonium sulfate precipitation and Sephadex G-150 chromatography. Components isolated, as well as some enzymes present in the culture, were assayed for toxicity by feeding to white mice. Early work indicated that when a meat-fat-starch slurry, infected with C. perfringens, was fed to mice, the intestinal passage time was reduced. By using large numbers of mice as test animals and analyzing the data statistically, we found that C. perfringens and several fractions from the culture supernatant significantly affected the mice. A toxic material present in the supernatant was not identifiable as phospholipase C. Phospholipase C and physphorylcholine affected the intestinal passage time of the mice only when large amounts were given. The enzyme, neuraminidase, and another unidentified compound present in the supernatant affected the passage time when very small amounts were fed to mice.